2017
DOI: 10.1101/133983
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Initial-state-dependent, robust, transient neural dynamics encode conscious visual perception

Abstract: Recent research has identified late-latency, long-lasting neural activity as a robust correlate of conscious perception. Yet, the dynamical nature of this activity is poorly understood, and the mechanisms governing its presence or absence and the associated conscious perception remain elusive. We applied dynamic-pattern analysis to whole-brain slow cortical dynamics recorded by magnetoencephalography (MEG) in human subjects performing a threshold-level visual perception task. Up to 1 second before stimulus ons… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…Behaviorally, stronger TTV reduction is associated with faster reaction time (He, 2013), superior perceptual abilities (Arazi, Gonen-Yaacovi, & Dinstein, 2017;Baria, Maniscalco, & He, 2017;Schurger et al, 2015), and superior memory recall (Xue et al, 2010). Therefore, it is plausible to assume that neuronal mechanisms involved in TTV reduction contribute to the disambiguation of environmental signals and enhance the efficiency of cortical information processing (Churchland et al, 2010;Finn et al, 2007;Monier et al, 2003;White et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Behaviorally, stronger TTV reduction is associated with faster reaction time (He, 2013), superior perceptual abilities (Arazi, Gonen-Yaacovi, & Dinstein, 2017;Baria, Maniscalco, & He, 2017;Schurger et al, 2015), and superior memory recall (Xue et al, 2010). Therefore, it is plausible to assume that neuronal mechanisms involved in TTV reduction contribute to the disambiguation of environmental signals and enhance the efficiency of cortical information processing (Churchland et al, 2010;Finn et al, 2007;Monier et al, 2003;White et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…György Buszáki (Buzsáki, 2019) suggests an alternative approach, ‘inside-out’; unlike the traditional ‘outside-in’, it places intrinsic neural activity as a key factor (inside) in modulating activity change related to external stimuli (outside) (see also Northoff et al 2010, Northoff 2014a and b). Consistent with this approach (Buzsáki, 2019), studies (He, 2013; Baria et al, 2017; Huang et al, 2017; Nieus et al, 2018; Galindo-Leon et al, 2019; Hirschmann et al, 2019; Podvalny et al, 2019) have demonstrated that poststimulus activity levels depend on the initial state, the level of prestimulus activity (Yamagishi et al, 2008; Mathewson et al, 2009; Northoff et al, 2010; Fellinger et al, 2011; Hanslmayr et al, 2013; He, 2013; Milton and Pleydell-Pearce, 2016; Benwell et al, 2017; Huang et al, 2017; Hirschmann et al, 2019). These findings demand the question: how and in what way do prestimulus activity levels shape stimulus-induced activity beyond the external stimulus?…”
Section: Introductionmentioning
confidence: 72%
“…The brain's spontaneous activity exhibits fluctuations in different frequency ranges. These include faster frequencies from 1Hz to 240Hz 23 as well as slower ones like the slow cortical potentials (0.1hz to 1Hz) which all can be measured using EEG or MEG [24][25][26][27][28] . These different frequencies have been associated with diverse functions including perception, attention, working memory, self, motivation, and consciousness (and various others) 23,29 .…”
Section: Introductionmentioning
confidence: 99%